Characteristics of epidermal growth factor receptor (EGFR)-Mutated Non Small Cell Lung Carcinoma (NSCLC)-patients who developed resistance to first or second generation Egfrtyrosine Kinase Inhibitor (TKI) Therapy through T790M mutation / Vijayan Munusamy - Vijayan, Munusamy (2017)
The management of non-small cell lung cancer (NSCLC) has undergone a major revolution in diagnosis and treatment over the past few years. The detection of epidermal growth factor receptor (EGFR) mutation has enable advanced NSCLC to be treated with EGFR-tyrosine kinase inhibitors (TKls). However, most patients treated with first- or second-generation EGFR-TKls inevitably develop acquired resistance and disease progression. Objectives This study was conducted to determine the incidence of T790M mutation as an acquired resistance mechanism in patients with advanced EGFR-mutant NSCLC who have developed disease progression while on first- or second-generation EGFR-TKI therapy, and the clinical characteristics of such patients while being treated at the University of Malaya Medical Centre. This study also aimed to compare the clinical characteristic of patients with acquired T790M mutation, causing resistance to first-line EGFR-TK I treatment, with that of patients who develop resistance to first-line EGFR-TKI treatment not due to acquired T790M mutation. Methods: This retrospective observational study evaluated EGFR-mutant advanced NSCLC patients on EGFR-TKI therapy who have developed disease progression during the period from 1st August 2015 to 211d August 20 17 at University of Malaya Medical Centre. Patients with disease progression according to Jackman's criteria underwent liquid and/or tissue re-biopsy to detect the secondary T790M mutation in exon 20 of the EGFR gene. Results: The data from a total of 68 patients who met the study inclusion criteria were analysed. Six patients underwent only liquid biopsy 36 patient underwent tissue re-biopsy and 15 underwent liquid biopsy and 11 tissue re-biopsy. Out of the 68 patients studied, T790M mutation was detected in 35 patients (51.4° o). T790M mutation was detected in the plasma of I 0 patients in tissue re- biopsy specimens of 20 patients and in both the plasma and tissue re-biopsy specimens of 5 patients. From the total of 68 patients, 57 (84.0%) were treated with first-generation EGFR-TKI and II were treated with second generation EGFR-TKI. Patients treated with first-generation EGFR-TKI were less likely to develop T790M mutation compared to those treated with second-generation EGFRTKI (52.6% vs 45.5%, p=0.9 15). The duration of first-line EGFR-TKI treatment was numerically longer in those patients who acquired T790M mutation (l 3.8 months) compared to those who did not (II. I months) (p =0.21). A higher proportion of patients who did not acquire T790M mutation had a better ECOG performance status of 0-1 (60.6%) at the time of disease progression compared to those who developed progression due to acquired T790M mutation (28.6%) (p=0.028). Conclusions: T790M mutation was identified as the acquired resistance mechanism causing first-line EGFR-TKI treatment failure in 51.4% of our patients. There was no difference in the clinical and treatment characteristics between patients with or without acquired T790M mutation as the cause of resistance to first-line EGFR-TKI treatment. At the time of disease progression, compared to patients with acquired T790l\1 mutation a significantly higher proportion of patients who did not h:\\ c acquired T790M mutation had a better ECOG performance status. The duration of first-line EGFR-TKI treatment was longer in those patients who acquired T790M mutation compared to those who did not.